Cinema com mulheres em Pernambuco: trajetórias, políticas, estética - Galvão, Yanara Cavalcanti (2018)
The present work proposes to investigate different resignifications of the feminine in its relation with the cinematographic field to think about the corpus of this research: the cinema with women in Pernambuco. To do so, it traverses trajectories of women and the cinemas that cross them, on the margins of the logic of the hegemonic model of cinema and its classical historiography. Thus, assuming the gap and desmemory that marked the cinematographic and historical process for women, the study was prepared to (re) constitute traces of these paths. In a first moment, it accompanies the movements of the women and their historical narratives by the feminist perspective. From the belated legitimization of the category of women, to the processes of rupture with essentialist ideas of the feminine, cinema with women begins to be approached, also passing through the first incursions of the filmmakers in the filmic realization, in the national and local contexts. With this contextualization, in a second moment of this study, a dialogue is drawn with the political articulations and participation in the construction of public policies by the women workers of the cinema. In this way, we seek to understand how the contemporary independent film scene being held in Pernambuco is constituted. Finally, it is proposed to think of a contemporary cinema in movement and in transformation, with women. The selected films, besides the female authorship, contemplate experiences marked by difference, reflected in their spaces of sharing, aesthetic powers and political gestures, confronting the common places of representation. This film study is interdisciplinary in nature and draws on theoretical contributions in dialogue and specific incursions into feminist theories, in different epistemological fields, such as Cultural Studies, Post-Structural Studies, Postcolonial Studies, Cinema, Aesthetics and Politics.